Analyses of children's mathematics proficiency from ECLS-K 1998 and 2010 cohorts: Why early mathematics?. (March 2017) - Lee, Joohi; Pant, Mohan D.
This article presents the correlation analyses of mathematics item response theory scores from the Early Childhood Longitudinal Study, Kindergarten Class of 1998 and 2010 data, and proposes the critical need for systematic efforts to improve the quality of pre- and in-service teachers of young children in teaching mathematics.